2015
DOI: 10.1210/en.2014-1978
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Increases Preovulatory LH Source and the Number of Mature Follicles, As Well As Synchronizing the Onset of Puberty in Female Rats

Abstract: Control of estrous cycle and reproductive capacity involves a large number of central and peripheral factors, integrating numerous nutritional and metabolic signals. Here we show that glucagon-like peptide-1 (GLP-1), a peptide with anorexigenic and insulinotropic actions, and the GLP-1 receptor agonist Exendin-4 (Ex4) exert a regulatory influence on the gonadal axis, in both adult and prepubertal female rats. In adult rats, Glp-1 receptor expression varies during the estrous cycle at the hypothalamus, pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 49 publications
2
56
1
Order By: Relevance
“…The intracellularly applied NO-scavenger CPTIO, the TRPV1 inhibitor AMG9810 and the FAAH inhibitor PF3845 were effective, too, confirming further the direct action of Exendin-4 in GnRH neurons. Thus, direct effect of GLP-1 agonist on GnRH neurons is revealed beside its earlier suggested indirect action via kisspeptin neurons (Outeiriño-Iglesias et al, 2015). …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The intracellularly applied NO-scavenger CPTIO, the TRPV1 inhibitor AMG9810 and the FAAH inhibitor PF3845 were effective, too, confirming further the direct action of Exendin-4 in GnRH neurons. Thus, direct effect of GLP-1 agonist on GnRH neurons is revealed beside its earlier suggested indirect action via kisspeptin neurons (Outeiriño-Iglesias et al, 2015). …”
Section: Discussionmentioning
confidence: 90%
“…Our data are in accordance with a recent investigation showing stimulatory effect of GLP-1 in neurons of the paraventricular nucleus, the bed nucleus of the stria terminalis and the hippocampus (Cork et al, 2015). Excitatory role of GLP-1 on the reproductive axis has already been suggested, too (Beak et al, 1998; MacLusky et al, 2000; Outeiriño-Iglesias et al, 2015). Our finding is also supported by other studies showing increased spike and mPSC frequency in hypothalamic hypocretin/orexin neurons (Acuna-Goycolea and van den Pol, 2004) or revealing elevated c-fos level and firing rate in neurons of parabrachial nucleus (Richard et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Functional studies indicate that GLP-1 promotes GnRH secretion from isolated hypothalamic tissue and acts centrally to enhance LH levels in male rats (Beak et al, 1998). More recent studies demonstrate that GLP-1 acts centrally to enhance the preovulatory LH surge of intact female rats (Outeirino-Iglesias et al, 2015). Taken together, these data suggest that GLP-1 promotes GnRH/LH release.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in humans with short-term infusions of GLP1Ra showed only transient increases in circulating levels of ACTH and cortisol [148] . Recent studies demonstrated the effects of exendin-4 on the hypothalamic-pituitary-adrenal axis with secretion of corticosteroids in male mice [149] and in the reproduction of female mice by increases in LH and the number of mature follicles [150]. Despite the presence of GLP-1R in culture of parafollicular C-cell tumors, the use of GLP1Ra was not associated with the diagnosis of medullary thyroid carcinoma in humans [83,151] Since the beginning of incretin-based therapy in T2DM patients, questions remain about the use of this therapy in T1D patients [152] .…”
Section: -New Discoveries About Glp-1mentioning
confidence: 99%